The role of infliximab in treating refractory cardiac sarcoidosis. Case series and systematic review of literature: Infliximab use in cardiac sarcoidosis - Ahmed, Raheel; Okafor, Joseph; Khattar, Rajdeep; Azzu, Alessia; Baksi, John; Wechalekar, Kshama; Sharma, Rakesh; Wells, Athol; Kouranos, Vasilis (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Cardiac sarcoidosis is associated with significant morbidity and mortality. Immunosuppressive treatment focuses on suppressing myocardial inflammation, which can lead to major adverse events especially when progressing to fibrosis. Conventional management usually includes steroids and steroid sparing agents such as methotrexate and azathioprine. Tumour necrosis factor alpha inhibitors are often reserved for those with a worsening clinical status and/or evidence of persistent inflammatory activity despite conventional therapy. Refractory cardiac sarcoidosis (CS) can be defined as the persistence or progression of active disease, evidenced either by lack of clinical response or persistence or progression of imaging abnormalities, despite being on conventional therapy. In the United Kingdom, tumour necrosis factor alpha inhibitors are currently not licensed for cardiac sarcoidosis as there are no randomised controlled trials to assess the efficacy of infliximab in this patient cohort. In this study, we present the outcomes of six patients treated with infliximab for refractory cardiac sarcoidosis at Royal Brompton Hospital and performed a systematic review of the existing literature on use of infliximab in cardiac sarcoidosis. We searched the Cochrane Library, OVID Medline, OVID Embase, Web of Science and Pubmed to identify 7 full-text studies assessing the role of infliximab in the management of cardiac sarcoidosis. Infliximab was found to play a vital role in stabilising refractory cardiac sarcoidosis by stemming clinical deterioration, arrythmia burden and even reducing steroids requirements. Further prospective trial data is necessary to validate these findings.